Chemosensitization of multidrug resistant Candida albicans by the oxathiolone fused chalcone derivatives - Łącka, Izabela; Konieczny, Marek T.; Bułakowska, Anita; Kodedova, Marie; Gaskova, Dana; Maurya, Indresh K.; Prasad, Rajendra; Milewski, Slawomir (Frontiers in Microbiology, 2015)
Three structurally related oxathiolone fused chalcone derivatives appeared effective chemosensitizers, able to restore in part sensitivity to fluconazole of multidrug-resistant C. albicans strains. Compound 21 effectively chemosensitized cells resistant due to the overexpression of the MDR1 gene, compound 6 reduced resistance of cells overexpressing the ABC-type drug transporters CDR1/CDR2 and derivative 18 partially reversed fluconazole resistance mediated by both types of yeast drug efflux pumps. The observed effect of sensitization of resistant strains of Candida albicans to fluconazole activity in the presence of active compounds most likely resulted from inhibition of the pump-mediated efflux, as was revealed by the results of studies involving the fluorescent probes, Nile Red, Rhodamine 6G and diS-C3(3).